The essential HR handbook a quick and handy resource for any manager or HR professional - Armstrong, Sharon (Franklin Lakes Career Press, 2008)
Whether you are a newly promoted manager, a seasoned business owner, or a human resources professional, knowing the ins and outs of dealing with HR issues is critical to your success. The Essential HR Handbook is a quick-reference guide that sheds light on the issues that keep managers up at night. It is filled with information, tools, tips, checklists, and road maps to guide managers and HR professionals through the maze of people and legal issues, from recruiting and retaining the best employees to terminating poor performers. With this book, you'll learn how to effectively and efficiently: Individually manage each employee, starting on his or her first day. Manage a multi-generational workforce. Appraise job performance. Coach and counsel. Provide equitable pay, benefits, and total rewards strategies. Identify legal pitfalls and stay out of court.
Includes bibliographical references (p. 240-248)
Keywords: Personnel management